FAKTOR- FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT - Lestari, Winda; Rizany, Ichsan; Setiawan, Herry (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2021)
ABSTRACT The low quality of service so that the level of patient satisfaction has not met the minimum service criteria, namely 95% which is influenced by several factors so that the degree of satisfaction is still low.Objective: to find out the factors that influence the satisfaction level of swamp patients in hospitalMethods: This study uses a literature review, from two electronic databases; Google Scholar and Garuda in the period 2010-2020 found ten literatures that match keywords.Results: The results of data synthesis in 10 journal articles 5 journal articles stated that the level of patient satisfaction was low due to ineffective communication, 4 journal articles stated that the level of satisfaction was low because of the quality of service, and 1 journal article stated that the level of patient satisfaction was low due to official scheduling.Discussion: Patient satisfaction with the quality of service provided by nursing personnel to clients while receiving hospital care, services, and nursing care received by patients is a form of professional service that can increase inpatient satisfaction and improve the quality of health services. Keywords: Patient, Hospitalization, Satisfaction Level.